A more accurate indicator to evaluate oxidative stress in rat plasma with osteoporosis. Issue 2 (5th January 2023) - Dong, Wei-Chong; Guo, Jia-Liang; Jiang, Xin-Hui; Xu, Lei; Wang, Huan; Ni, Xiao-yu; Zhang, Ying-Ze; Zhang, Zhi-Qing; Jiang, Ye
Abstract : A simple and accurate HFCF-UF as preparation procedure for the first time was used to analyze homocysteine, cysteine, and homocystine, cystine simultaneously. Hcy reduced/oxidized is a more accurate indicator to evaluate oxidative stress. Abstract : Background : oxidative stress is linked to various human diseases which developed into the idea of "disrupted redox signaling". Osteoporosis (OP) is a chronic skeletal disorder characterized by low bone mineral density and deterioration of bone microarchitecture among which estrogen deficiency is the main cause. Lack of estrogen leads to the imbalance between oxidation and anti-oxidation in patients, and oxidative stress is an important link in the pathogenesis of OP. The ratio of the reduced to the oxidized thiols can characterize the redox status. However, few methods have been reported for the simultaneous determination of reduced forms and their oxidized forms of thiols in plasma. Methods : we developed a hollow fiber centrifugal ultrafiltration (HFCF-UF) method for sample preparation and validated a high-performance liquid chromatography tandem mass spectrometry (HPLC-MS/MS) method to determine two reduced forms of thiols-homocysteine (Hcy), cysteine (Cys) levels and their respective oxidized compounds, homocystine (HHcy) and cystine (Cyss) in rat plasma simultaneously for the first time. Thirty-six female rats were randomly divided into three groups: normal control (NC), oxidative stress (ovariectomy, OVX) and ovariectomy with hydrogen-rich saline administration (OVX + HRS). Results : the validation parameters for the methodological results were within the acceptance criteria. There were both significant differences of Hcy/HHcy (Hcy reduced/oxidized) and Cys/Cyss (Cys reduced/oxidized) in rat plasma between three groups with both p < 0.05 and meanwhile, the p values of malondialdehyde, superoxide dismutase and glutathione peroxidase were all less than 0.01. The value of both Hcy/HHcy and Cys/Cyss were significantly decreased with the change of Micro-CT scan result of femoral neck in OVX group (both the trabecular thickness and trabecular number significantly decreased with a significant increase of trabecular separation) which demonstrate OP occurs. The change of Hcy/HHcy is more obvious and prominent than Cys/Cyss. Conclusions : the Hcy/HHcy and Cys/Cyss could be suitable biomarkers for oxidative stress and especially Hcy/HHcy is more sensitive. The developed method is simple and accurate. It can be easily applied in clinical research to further evaluate the oxidative stress indicator for disease risk factors.